2021 Comprehensive Surveillance Review : Background Paper on The Surveillance Priority Preempting and Mitigating Spillovers. (Policy Papers; Policy Paper, 2021)
The Fund has a range of modalities and tools to cover spillovers. However, there remains scope to enhance synergies between global and country-specific spillover coverage and to foster cross-country dialogue. Practical guidance and enhanced information-sharing would also allow for more systematic surveillance of spillovers. Furthermore, the COVID-19 pandemic has underscored the need to continue expanding the research frontier covering new spillovers and channels and developing new tools and data sets. Therefore, filling these remaining gaps in the Fund's spillover work would allow for a more coordinated and evenhanded surveillance of spillovers.